2022
DOI: 10.48048/tis.2022.2669
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aromatherapy Inhalation on Reducing Chronic Pain for Children with Cancer: A Pilot Study

Abstract: Chronic pain is a physical symptom often experienced by pediatric patients with cancer. Long-lasting pain conditions can cause the deterioration of the quality of life of children. In order to enhance their quality of life, they should get any intervention to control the pain. Besides the pharmacologic pain management, nurses also should develop a non pharmacologic pain management strategy. One of the simplest and cheap strategy which is currently being developed was aromatherapy. This study aims to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Triana and collaborators in 2022 [ 82 ] perform a quasi-experimental study with a consecutive sampling technique with the purpose of understanding the effectiveness of aromatherapy in school-age children and adolescents (7–17 years) with a diagnosis of cancer, experiencing chronic pain (for longer than 1 month) and receiving moderate analgesics/opioids. A sample of 20 patients are randomly allocated to two groups: Intervention (N = 10), consisting in aromatherapy with the most favored scent (most often aloe vera) and Control (N = 10) with standard care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Triana and collaborators in 2022 [ 82 ] perform a quasi-experimental study with a consecutive sampling technique with the purpose of understanding the effectiveness of aromatherapy in school-age children and adolescents (7–17 years) with a diagnosis of cancer, experiencing chronic pain (for longer than 1 month) and receiving moderate analgesics/opioids. A sample of 20 patients are randomly allocated to two groups: Intervention (N = 10), consisting in aromatherapy with the most favored scent (most often aloe vera) and Control (N = 10) with standard care.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis, including six out of twelve studies included in synthesis (forest plot reported in Figure 3 ), demonstrates statistically significant efficacy of the use of essential oils in the reduction of the intensity of pain associated with cancer, assessed through unidimensional pain scales ( p = 0.002). In particular, the studies contribute almost equally to the results, apart from the study performed by Triana and collaborators [ 82 ], which has a lower weight because of the reduced sample size and because it presents wider standard deviation. Moreover, it is possible to highlight high heterogeneity among the studies eligible for the meta-analysis (I 2 = 96%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selain itu penggunaan aromaterapi juga memiliki efek positif lainnya, seperti peningkatan kualitas tidur, perasaan rileks dan berkurangnya frekuensi penggunaan obat analgesik tambahan. (Triana et al, 2022).…”
unclassified